Synthesis and structural features of 5-(4-(tert-butyl) phenyl)-4-((R)amino)-4H-1,2,4-triazole-3-thiols - I. I. Aksyonova-Seliuk; O. I. Panasenko; E. G. Knysh (Фармацевтичний журнал, 2018)
Chemistry of heterocyclic compounds is one of the most popular sector in organic chemistry. Scientists allocate among them a class of derivatives of 1,2,4-triazole. This class of compounds attracts attention his broad spectrum of biological activity. There are antiviral, anti-inflammatory, anti-tubercular, antimicrobial, antioxidant, actoprotective, anti-cancer and other activities. The derivatives of 1,2,4-triazole have one more important advantage. It is low toxicity. This properties do this class of derivatives promising for researches their chemical structure and biological activity and purposeful search of biologically active substances.